2020
DOI: 10.2147/idr.s279020
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efflux Pump AcrAB Confers Decreased Susceptibility to Piperacillin–Tazobactam and Ceftolozane–Tazobactam in Tigecycline-Non-Susceptible <em>Klebsiella pneumoniae</em></p>

Abstract: Introduction Drug efflux pumps are critical for resistance in Gram-negative organisms, but there are limited data on the role they play in decreased susceptibility to β-lactam/β-lactamase inhibitor combinations. In this study, we aimed to investigate the impact of efflux pump AcrAB on piperacillin–tazobactam (TZP) and ceftolozane–tazobactam (C/T) susceptibility in tigecycline-non-susceptible Klebsiella pneumoniae (TNSKP) strains. Methods A tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Piperacillin/tazobactam, ceftazidime, cefepime and carbapenem resistance in P. aeruginosa has been associated with ampC (PDC, Pseudomonas derived cephalosporinase) derepression, OprD loss (imipenem >meropenem), and/or hyperexpression of efflux pumps (meropenem, not imipenem) [13,28]. OprD porin loss and the majority of known efflux pumps do not alter ceftolozane/tazobactam MICs [13,18,28,29]. Rarely, P. aeruginosa may develop resistance to ceftolozane/tazobactam and ceftazidime/avibactam during treatment when an isolate acquires mutation(s) that highly de-repress expression of PDC [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Piperacillin/tazobactam, ceftazidime, cefepime and carbapenem resistance in P. aeruginosa has been associated with ampC (PDC, Pseudomonas derived cephalosporinase) derepression, OprD loss (imipenem >meropenem), and/or hyperexpression of efflux pumps (meropenem, not imipenem) [13,28]. OprD porin loss and the majority of known efflux pumps do not alter ceftolozane/tazobactam MICs [13,18,28,29]. Rarely, P. aeruginosa may develop resistance to ceftolozane/tazobactam and ceftazidime/avibactam during treatment when an isolate acquires mutation(s) that highly de-repress expression of PDC [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The major genetic regulators of these two pumps are RamA and RarA, respectively, together belonging to the AraC-type transcriptional regulators in K. pneumoniae , [ 46 , 47 ]. AcrAB is involved in the efflux of various antibiotics including the most recent broad-spectrum antibiotics, such as piperatazocillin or ceftolozane-tazobactam, and OqxAB expels fluoroquinolones, tigecyclin and nitrofurantoin [ 45 ]. Concerning the detection of efflux mechanisms and their prevalence in the resistance of clinical strains, Kareem et al showed that 27 of the 43 selected MDR K. pneumoniae clinical strains presented an efflux activity by using an EtBr-agar cartwheel screening method [ 48 ].…”
Section: Clinical Impact Situationmentioning
confidence: 99%
“…The oqxAB operon was originally described on plasmid carried by an E. coli strain conferring resistance to chloramphenicol and quinolones [44]. In K. pneumoniae, it is associated with the resistance of quinoxalines, quinolones, tigecycline, nitrofurantin and chloramphenicol [45]. The major genetic regulators of these two pumps are RamA and RarA, respectively, together belonging to the AraC-type transcriptional regulators in K. pneumoniae, [46,47].…”
Section: Enterobacteriaceaementioning
confidence: 99%
“…aureus: USA300 genome GCA 000013465.1 [51] and the TW20 genome GCA 000027045.1 [52]. K. pneumoniae: GCF 000784945 [53], GCF 001952915 [54], GCF 003073315, GCF 003076555 [55], and GCF 011006575 [56].…”
Section: Data Availabilitymentioning
confidence: 99%
“…K. pneumoniae : GCF_000784945[53], GCF_001952915[54], GCF_003073315, GCF_003076555[55], and GCF_011006575[56].…”
Section: Data Availabilitymentioning
confidence: 99%